Sectoral engines of growth in South Africa: An analysis of services and manufacturing - Fiona Tregenna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Manufacturing has traditionally been regarded in the development literature as having special growth-pulling or growth-enhancing properties. The share of manufacturing in GDP has been declining slightly over time in South Africa, while that of services has been growing. This study focuses on the Hirschmanian channels through which sectoral growth can lead or support aggregate economic growth, using input-output tables to investigate intersectoral linkages in the South African economy. Manufacturing is found to be especially important as a source of demand for the services sector and the rest of the economy through its strong backward linkages. This draws attention to possible negative implications of a decline in manufacturing on the South African economy.
Keywords: D57; L60; L80; O14; 330; growth; manufacturing; services; multipliers; input-output tables; South Africa; Wirtschaftswachstum; Branchenentwicklung; Dienstleistungssektor; Verarbeitendes Gewerbe; Südafrika